The Existence of Students with Special Needs in an Inclusive Elementary School - Silvita; Hermanto (Jurnal Ilmiah Sekolah Dasar, 2023)
Children with special needs at school receive less attention from teachers at school. The study aimed to describe the classroom teacher's views on children with special needs, children's adjustment to learning, expressing children's interactions with obstacles, and child development. This type of research uses qualitative research with a descriptive qualitative approach. This research was carried out through design, research, implementation, data analysis, and making research reports. Data collection techniques using interviews, observation, and documentation. The research subjects were 17 children with special needs; the data source came from 10 teacher respondents, namely 7 class teachers, 2 subject teachers, and 1 special supervising teacher. Data analysis is done by gathering information through data reduction, display, and conclusions. The results of this study show that teachers at school do not feel ready to handle children with special needs, but the environment is supportive, teachers can learn how to deal with children, and teachers can create a positive attitude. Learning at school is carried out by adjusting to the needs of children and is carried out comfortably. Teachers at school do not discriminate between students with special needs and regular children. Interactions carried out by children with special needs with regular children are carried out well under the guidance of teachers at school. The surrounding environment helps children with disabilities develop properly.